Bridging therapies for patients with hepatocellular carcinoma awaiting liver transplantation: A systematic review and meta‐analysis on intention‐to‐treat outcomes. (22nd October 2022) - Di Martino, Marcello; Ferraro, Daniele; Pisaniello, Donatella; Arenga, Giuseppe; Falaschi, Federica; Terrone, Alfonso; Maniscalco, Marilisa; Galeota Lanza, Alfonso; Esposito, Ciro; Vennarecci, Giovanni
Abstract: Introduction: Locoregional therapies are commonly used as bridging strategies to decrease the drop‐out of patients with hepatocellular carcinoma (HCC) awaiting liver transplantation (LT). The present paper aims to assess the outcomes of bridging therapies in patients with HCC considered for LT according to an intention‐to‐treat (ITT) survival analysis. Material and methods: Medline and Web of Science databases were searched for reports published before May 2021. Papers assessing adult patients with HCC considered for LT and reporting ITT survival outcomes were included. Two reviewers independently identified, extracted the data, and evaluated the papers according to Newcastle‐Ottawa criteria. Outcomes analyzed were: drop‐out rate; time on the waiting list; 1‐, 3‐, and 5‐year survival after LT and based on an ITT analysis. Results: The search identified 3106 records; six papers (1043 patients) met the inclusion criteria. Patients with HCC, listed for LT and submitted to bridging therapies presented a longer waiting time before LT (MD 3.77, 95% CI 2.07‐5.48) in comparison with the non‐interventional group. However, they presented a raised post LT after 1‐year (OR 2.00, 95% CI 1.18‐3.41), 3‐years (OR 1.47, 95% CI 1.01‐2.15), and 5‐years (OR 1.50, 95% CI 1.06‐2.13) survival. Conclusion: Patients submitted to bridging procedures, despite having a longer interval on the waiting list, presented better post‐LT survival outcomes. Bridging therapies for selected patients at low risk of post‐procedural complications and long expected intervals on the waiting list should be encouraged. However, further clinical trials should confirm the survival benefit of bridging therapies in patients with HCC listed for LT. Abstract : Di Martino and colleagues conducted a meta‐analysis to assess the outcomes of locoregional therapies as bridging strategies in patients with hepatocellular carcinoma considered for liver transplantation. Patients submitted to bridging, despite a longer interval on the waiting list, presented better post‐transplant survival outcomes, suggesting that bridging therapies should be encouraged.